1974
DOI: 10.1677/joe.0.0620431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Reduction in Milk Removal From Some Glands Upon the Ability of a Single Rabbit Mammary Gland to Secrete Milk

Abstract: Milk yield fell in a single rabbit mammary gland within 24 h after the litter had been reduced from six to eight pups to one pup. The diminished secretion lasted 2\p=n-\3 days, then rebounded to the expected level over the next 1\p=n-\2 days and thereafter maintained this level. During early to mid-lactation the decrease in milk secretion after reduction of the litter to one pup was prevented either by s.c. injections of prolactin or by s.c. injections of the \g=b\-adrenergicblocking drug, propranolol. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…But he offered no statistical treatment of the results which makes interpretation difficult. Mena, Reyes, Aguayo & Grosvenor (1974) in a complex series of experiments also suggested that tissue sensitivity to circulating prolactin diminishes as lactation progresses. At present no firm data exist to indicate whether prolactin secretion decreases, whether tissue sensitivity declines, or whether both processes occur and this problem will probably not be solved until a method becomes available for the determination of plasma prolactin concentrations in the rabbit.…”
Section: Effects Of Prolactinmentioning
confidence: 99%
See 1 more Smart Citation
“…But he offered no statistical treatment of the results which makes interpretation difficult. Mena, Reyes, Aguayo & Grosvenor (1974) in a complex series of experiments also suggested that tissue sensitivity to circulating prolactin diminishes as lactation progresses. At present no firm data exist to indicate whether prolactin secretion decreases, whether tissue sensitivity declines, or whether both processes occur and this problem will probably not be solved until a method becomes available for the determination of plasma prolactin concentrations in the rabbit.…”
Section: Effects Of Prolactinmentioning
confidence: 99%
“…It has previously been argued that the passage of ['4C]sucrose from blood to milk is a measure of paracellular movements across the mammary epithelium c, 1974. Therefore the passage of [F4C]sucrose, 24Na and 36C0 from blood to milk was studied in four prolactin-treated rabbits, 12 hr after the last injection.…”
Section: Effects Of Prolactin In Late Lactationmentioning
confidence: 99%
“…In addition, release of PRL by suckling in rabbits accounts for high milk yields during early lactation and for maintenance of lactation (Mena et al, 1974;Taylor and Peaker, 1975). Moreover, PRL exerts a direct effect (secretagogue effect) on the release of caseins by epithelial mammary cells (Ollivier-Bousquet, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…prevent the changes in composition and yield [Gachev, 1963a[Gachev, , 1965[Gachev, , 1971aCowie, 1969;Linzell, Peaker and Taylor, 1975], it has been suggested that either the release of prolactin is less in late lactation [Cowie, 1969] or the sensitivity of the mammary tissue to prolactin is reduced [Gachev, 1971a;Mena, Reyes, Aguayo and Grosvenor, 1974]. Recently, McNeilly andFriesen [1977, 1978] have developed a radioimmunoassay for rabbit prolactin and have found that the amount appearing in plasma in response to suckling decreased as lactation advanced.…”
mentioning
confidence: 99%